The relationship between chemerin levels and carotid intima-media thickness in patients with ischemic stroke - Demir, Caner; Atas, Iklimya; Aytac, Emrah; Gonen, Murat; Erten, Zeynep (Lippincott Williams & Wilkins, 2017)
[Abstract Not Available]